Kansas PRIDE 2009 Annual Review - Kahl, Dan; Rice, Trudy; Stinson, Jeanne; Burton, Josh (My University, 2009)
Summary of the 2009 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development